METODE EXPERIENTIAL LEARNING DAN IMPLEMENTASINYA PADA MATA PELAJARAN IPS PADA PESERTA DIDIK SDN 3 BEDRUG TAHUN PELAJARAN 2022/2023 - Titin Sundari; Arif Hadi Prasetyo; Endang Sri Maruti (STKIP Subang, 2023)
Experiential learning or experience-based learning is a learning method that emphasizes challenges followed by reflection on the learning outcomes obtained from the experience. Social studies learning in elementary schools emphasizes the achievement of good citizens so that to be able to realize these goals, a real action is needed in learning so that students have real experience related to the material learned. The results of this study were analyzed by multiple regression analysis where students' ability to understand social studies experiential learning methods obtained a value range of 45 49 as much as 36.7%. The value range of 51 55 is 63.3%. Then the level of student understanding obtained a range of values 45 48 as much as 23.3%, a range of values 49 52 as much as 46.7%, and a range of values 53 56 as much as 30%. The achievement of student learning outcomes obtained a range of values of 60 80 the number of 11 as much as 36.7%, a range of values 81 100 as much as 63.3%, and there is an influence between experiential learning on the ability to understand and its achievements in social studies subjects at SDN 3 Bedrug with a regression coefficient of variables X with Y1 of 0.3999, Tcalculate = 2.268 and sig. 0.031 < probability 0.05 and coefficient regression of variable X with Y1 of 0.3999, Tcalculate = 2.268 and sig. 0.031 < a probability of 0.05 and a regression coefficient of variable X with Y2 of 3.417, Tcalculate = 7.438 and sig. 0.000 < probability 0.05.